2019
DOI: 10.1016/j.econedurev.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The end of free college in England: Implications for enrolments, equity, and quality

Abstract: for their comments and suggestions. We also thank participants of the 2017 Higher Education, Funding & Access Seminar at the University of Edinburgh, and participants of the 2016 Northwestern University economics workshop for comments and suggestions. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…In this context, tuition subsidies appear as a simple tool to broaden college access. Our free college counterfactuals complement the literature on the recent free college policies in Chile (Bucarey 2018) and the elimination of free college in England (Murphy et al 2019). It also joins in the vast literature of college financial aid, 5 including the recent literature on free community college and the so-called "Promise" programs implemented in multiple U.S. states.…”
Section: Related Literaturesupporting
confidence: 52%
See 1 more Smart Citation
“…In this context, tuition subsidies appear as a simple tool to broaden college access. Our free college counterfactuals complement the literature on the recent free college policies in Chile (Bucarey 2018) and the elimination of free college in England (Murphy et al 2019). It also joins in the vast literature of college financial aid, 5 including the recent literature on free community college and the so-called "Promise" programs implemented in multiple U.S. states.…”
Section: Related Literaturesupporting
confidence: 52%
“…The abolition of free college has been implemented as an income-contingent loan from the government, which covers full per-student costs throughout college. Murphy et al (2019) show that the new system has led to higher enrollment, greater participation of lower-income students, and higher per-student funding.…”
Section: Discussionmentioning
confidence: 99%
“…5 These proportions are broadly in line with figures from other data sources. For example, Murphy et al (2019) report a university enrolment rate of around 38% for individuals aged 19-23 in 2008-09 (when most of the LSYPE respondents decided about higher education), based on the UK Labour Force Survey. subsequent GCSE performance (Strand, 2006;Betthäuser et al, 2020).…”
Section: Educational Performancementioning
confidence: 99%
“…However, a recent meta‐analysis concluded that students in the United States are more responsive to prices changes in higher education than European students (Havranek et al, ). Moreover, recent studies regarding the effect of specific reforms in tuition fees and student aid on enrolment found only modest or even no effects in Germany, the United Kingdom, and Denmark (Azmat & Simion, ; Baier & Helbig, ; Baumgartner & Steiner, ; Bruckmeier & Wigger, ; Dearden et al, ; Hübner, ; Murphy et al, ). Previous research has suggested that enrolment elasticity is rather weak in the Netherlands; there is a modest decrease in enrolment if the price of education increases (Canton & de Jong, ; Huijsman, Kloek, Kodde, & Ritzen, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Early research in the United States demonstrated that higher tuition fees and lower student aid are associated with diminishing enrolment in universities (Dynarski, ; Heller, ; Kane, ; Leslie & Brinkman, ). However, later research outside of the United States has indicated only modest or no effects of such reforms on enrolment (Azmat & Simion, ; Baier & Helbig, ; Bruckmeier & Wigger, ; Coelli, ; Dearden, Fitzsimons, & Wyness, ; Murphy, Scott‐Clayton, & Wyness, ; Nielsen, Sørensen, & Taber, ; Steiner & Wrohlich, ). Moreover, a recent meta‐analysis concluded that “the effect of tuition on enrolment is close to zero” (Havranek, Irsova, & Zeynalova, , p. 25).…”
Section: Introductionmentioning
confidence: 99%